Pemberdayaan Masyarakat melalui Pembuatan Pupuk Organik Cair di Desa Bulotalangi - Muhamad Bagus Kariri; Leonard Dharmawan; Iqbal Nurulhaq (Center for Alternative Dispute Resolution and Empowerment (CARE) IPB University, 2023)
Organic fertilizer serves as a crucial alternative in supporting sustainable plant growth, especially as a solution to the challenges posed by the high cost of chemical fertilizers and household waste management. The focus of community empowerment activities in Bulotalangi Village, Bone Bolango Regency, Gorontalo Province, is the production of liquid organic fertilizer from banana stem waste and rice washing water. Through interview methods, problem identification revealed that the cost of chemical fertilizers and household waste were major obstacles. Socialization and training involving 15 participants were conducted at the BUMDes Mo'otinelo hall on November 9, 2023. The outcomes of the activity include increased knowledge and skills of the community in transforming waste into liquid organic fertilizer. The fertilizer-making process involves banana stems, gamal leaves, rice washing water, brown sugar, and EM4. This training is expected to provide dual benefits: agricultural cost efficiency and household waste reduction, while enhancing soil fertility and farmers' income. The training also faced challenges in improving the community's understanding of the concept of liquid organic fertilizer. In conclusion, this community empowerment activity has successfully provided a sustainable local solution to support organic farming in Bulotalangi Village.